EXTH-63. EFFICIENT ADCC-MEDIATED KILLING OF MALIGNANT MENINGIOMA CELLS USING AVELUMAB AND AN ENGINEERED HIGH AVIDITY NATURAL KILLER CELL LINE, haNK. (5th November 2018) - Giles, Amber; Hao, Shuyu; Fuji, Rika; Padget, Michelle; Song, Hua; Zhang, Wei; Cao, Xiaoyu; Jung, Jinkyu; Liu, Yang; Jensen, Randy; Lee, John; Shiong, Patrick Soon; et al.
Abstract: BACKGROUND: Meningiomas are the most common primary brain tumor. Standard of care includes surgery and radiation therapy. There are no known effective medical therapies for recurrent meningioma, particularly for WHO grades II and III. As such, novel therapeutic approaches are desperately needed. PD-L1 is highly expressed in malignant meningioma, including the cell lines we tested, creating a potential target for ADCC-mediated killing. Therefore, we investigated the ability of avelumab, a PD-L1-specific antibody, to direct NK-mediated ADCC against malignant meningioma cells using healthy donor NK cells and the engineered NK cell line, haNK. METHODS: PD-L1 expression was assayed by flow cytometry and Western blotting in five human malignant meningioma cell lines. Avelumab-targeted ADCC was measured with healthy donor NK and haNK cells. Efficacy of avelumab+haNK was determined in vivo against meningioma implanted subcutaneously and orthotopically in a skull-base intracranial model. PD-L1 was deleted from tumor cells using CRISPR knockout to test specificity of the target. RESULTS: Avelumab directed healthy donor NK and haNK cells to mediate ADCC against all five meningioma cell lines in vitro . ADCC was enhanced by using NK cells with a high-avidity Fc receptor, haNK cells, or by upregulating PD-L1 in target cells. Avelumab+haNK significantly extended survival in mice bearing orthotopic meningioma and subcutaneous tumors. Conversely, killing (and survival benefit) was abrogated against cells in which PD-L1 was deleted. No toxicity was noted in pre-clinical models. CONCLUSIONS: We demonstrate that avelumab can target meningioma for ADCC by healthy donor NK cells, and killing is significantly enhanced with haNKs. haNK cells have demonstrated safety in humans, and avelumab has shown promising clinical activity in a variety of solid tumors. These data support the design of a clinical trial targeting PD-L1 with avelumab and haNK cells, potentially offering a novel immunotherapeutic approach for patients with malignant meningioma.